2015
DOI: 10.1097/igc.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality of Life in Patients With Endometrial Cancer Treated With Adjuvant Radiotherapy

Abstract: External beam radiotherapy negatively affects long-term QOL and sexual functions in endometrial cancer survivors. Vaginal BRT provides higher QOL. Patients with body mass index within normal limits have improved QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 19 publications
3
20
0
1
Order By: Relevance
“…Therefore the populations of EC survivors may also be expected to have higher BMI than the average population. In three of the descriptive studies where the participants answered a questionnaire concerning LLL, higher BMI was significantly associated with more LLL symptoms [34,42,44,45] while in other studies such an association between BMI and risk for LLL was not demonstrated [8,24,28,41,46]. Higher levels of physical activity have been associated with a significantly reduced risk for LLL.…”
Section: Risk Factors For Lllmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore the populations of EC survivors may also be expected to have higher BMI than the average population. In three of the descriptive studies where the participants answered a questionnaire concerning LLL, higher BMI was significantly associated with more LLL symptoms [34,42,44,45] while in other studies such an association between BMI and risk for LLL was not demonstrated [8,24,28,41,46]. Higher levels of physical activity have been associated with a significantly reduced risk for LLL.…”
Section: Risk Factors For Lllmentioning
confidence: 98%
“…A large retrospective Dutch study investigated the impact of LA with and without adjuvant RT on HQoL but found no clinically relevant differences in overall HQoL between the groups [61]. Karabuga et al showed negative effect on HQoL after external RT and vaginal brachytherapy with significantly more LLL symptoms after external RT [44].…”
Section: Impact On Hqolmentioning
confidence: 99%
See 1 more Smart Citation
“…They often report symptoms such as pain, diarrhea and lymphedema (70). LLL deeply impacts physical activity (71,72) and normal activities like walking, standing or house working.…”
Section: Impact On Quality Of Lifementioning
confidence: 99%
“…Risk factors remains to be evaluated in correctly designed and sufficiently powered studies. However, lymphadenectomy per se [4][5][6][7], number of lymph nodes removed [6,[8][9][10][11][12][13][14][15][16] and radiotherapy [3, [7][8][9][10][11]14,[17][18][19][20] seem to be established risk factor. Lymphedema onset may begin immediately after surgery or may be delayed for many years.…”
mentioning
confidence: 99%